LncRNA PCGsEM1 Contributes to the Proliferation, Migration and Invasion of Non-small Cell Lung Cancer Cells via acting as a Sponge for miR-152-3p - Huang, Jianhui; Lou, Jian; Liu, Xueni; Xie, Yanru (Current Pharmaceutical Design, 2021)
Background: Long non-coding RNAs (lncRNAs) have been reported to play important roles in cellular biological function. Aberrant expression of lncRNAs has been found to be related to the progression of various diseases. LncRNA prostate cancer gene expression marker 1 (PCGEM1) has been demonstrated to be involved in the initiation and progression of human cancers. However, to date, the clinical and functional significance of PCGEM1 expression in NSCLC progression remains unknown. Methods: The expression of LncRNA PCGEM1 and miR-152-3p in NSCLC tissues and cells was analyzed using quantitative real-time RT-PCR. Experiments using NSCLC cells were conducted to explore the influence of PCGEM1 on tumor cell proliferation, migration and invasion. Results: Increased expression of PCGEM1 was observed in NSCLC tissues and cells compared with the corresponding controls (all P < 0.001). PCGEM1 expression was associated with NSCLC patients’ lymph node metastasis and TNM stage (all P < 0.05), and the knockdown of PCGEM1 in NSCLC cells led to inhibited cell proliferation, migration and invasion. The further luciferase reporter assay and expression results showed that miR-152-3p might be a target gene of PCGEM1 and mediate the effects of PCGEM1 on cell proliferation, migration and invasion in NSCLC. Conclusion: Thus, the findings from the present study indicate that the NSCLC patients have significantly increased PCGEM1 and decreased miR-152-3p expression and that the knockdown of PCGEM1 may inhibit NSCLC cell proliferation, migration and invasion by sponging miR-152-3p. The PCGEM1/miR-152-3p axis may provide novel therapeutic targets for NSCLC treatment.
Keywords: non-small cell lung cancer